Maturing Singly Versus in Groups on Ovine Oocyte Meiosis - Endang Tri Margawati (Media Veteriner, 1998)
The effect of maturing systems (single vs groups) of ovine oocytes was studied to examine the oocyte development in vitro. Oocytes were aspirated from follicle ovaries collected at local abattoirs Cibinong West Java, using a 18-G needle. Aspiration medium consisted of H 199 + 2 % FCS + 50 μg/ml Heparin and the maturating medium (IVM) consisted of B 199 - 10 % FCS + 10 μg/ml FSH + 10 μg/ml hCG + 1 μg/ml Estradiol. The oocytes collected were divided into three groups and treated separately as follows: T1) oocytes were matured singly in 50 μl IVM medium. T2) every five oocytes was matured in 50 μl IVM medium and T3) every 10 oocytes was matured in 50 μl IVM medium. All oocytes were maintained in incubator with 5 % CO, and high humidity at 38 °C for 20 h. The resulting ova were stained in 1 % lacmoid then examined for meiosis division under a microscope. There was a signiticant effect among treatments on the proportion oocytes reaching metaphase II (P